2001
DOI: 10.1046/j.1440-1746.2001.02309.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis induced by Shou‐Wu‐Pian, a herbal product derived from Polygonum multiflorum

Abstract: Herbal preparations are widely available and generally regarded by the public as harmless remedies for a variety of medical ailments. We report the first case in Australia of acute hepatitis associated with the Chinese herbal medicine Shou-Wu-Pian, prepared from Polygonum multiflorum. Cholestatic hepatitis developed in a Chinese woman taking this preparation for the greying of her hair, and liver biopsy was consistent with a toxic reaction. Clinical and biochemical resolution occurred following cessation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 11 publications
(10 reference statements)
2
86
1
1
Order By: Relevance
“…Hepatic adverse effects have been reported since 1900s in China and other counties, and acute toxic hepatitis was the most common reported. Rash, fever, abdominal pain, dyspnea, vision problems and palpitations were common adverse effects of Polygonum Multiflorum [15,[40][41][42][43][44][45][46] . Pharmacokinetics and pharmacology studies of TSG will provide valuable information to ensure the safety and efficacies of TSG administration.…”
Section: Tsg Is the Major Bioactive Component Of Polygonum Multiflorummentioning
confidence: 99%
“…Hepatic adverse effects have been reported since 1900s in China and other counties, and acute toxic hepatitis was the most common reported. Rash, fever, abdominal pain, dyspnea, vision problems and palpitations were common adverse effects of Polygonum Multiflorum [15,[40][41][42][43][44][45][46] . Pharmacokinetics and pharmacology studies of TSG will provide valuable information to ensure the safety and efficacies of TSG administration.…”
Section: Tsg Is the Major Bioactive Component Of Polygonum Multiflorummentioning
confidence: 99%
“…ShouWu-Pian preparation is formulated from the root of Polygonum multiflorum plant (fleece flower root), which is a common Chines herb that belongs to Polygonaceae family (113,119). ShouWu-Pian is alternatively known as He-Shou-Wu and Mr. Black Hair (119,120). The roots and vines of P. multiflorum have been used as a tonic for treating several conditions including backache, constipation, dizziness, greying of hair, spermatorrhea, lumbago and treating symptoms of chronic prostatitis (120,121,122).…”
Section: Chinese Herbal Remediesmentioning
confidence: 99%
“…ShouWu-Pian is alternatively known as He-Shou-Wu and Mr. Black Hair (119,120). The roots and vines of P. multiflorum have been used as a tonic for treating several conditions including backache, constipation, dizziness, greying of hair, spermatorrhea, lumbago and treating symptoms of chronic prostatitis (120,121,122). Shou-Wu-Pian has been well known for its association with longevity and youthfulness (120).…”
Section: Chinese Herbal Remediesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction developed after an average of 20 weeks of therapy and was resolved in most patients in a mean of 8 weeks. The information enclosed with the preparation indicated that the product contained 30 % levoalkaloid from Polygala chinensis, but analysis suggested a more toxic substitute [21,22], an alkaloid from Stephania and Corydalis genera and not from Polygala [17].…”
Section: Substitution and Misidentification Of Herbal Substancesmentioning
confidence: 99%